Non-traumatic clostridial myositis: an unusual feature of brain death. Issue 657 (July 1980) - Thys, J. P.; Ectors, P.; Noel, P.
Abstract : In a case of brain death, a Clostridium sordellii and Escherichia coli septicaemia--of probable gastrointestinal origin--developed and was associated with a diffuse clostridial myositis. Factors responsible for the initiation and development of this unusual clostridial infection are discussed.